Safety Evaluation of MRI Magnetic Field Leakage from Different Configurations - Hong, Yap Siew; Nordin, Siti Aisyah Mohd; Kechik, Mohd Mustafa Awang; Karim, Muhammad Khalis Abdul; Ramli, Zarina; Baqjiah, Hussien; Chen, Soo Kien; Lim, Kean Pah; Shabdin, Muhammad Kashfi; Kamarudin, Aliah Nursyahirah; Doyan, Aris; Mohamed, Arebat Ryad Alhadei; Shaari, Abdul Halim (Journal of Material Science and Radiation, 2025)
Magnetic Resonance Imaging (MRI) systems generate intense static magnetic fields (SMFs), with fringe field propagation varying considerably between installations, even among scanners that operate at the same nominal field strength. This study investigates the safety implications of magnetic field leakage by quantifying and comparing SMFs distributions surrounding multiple MRI facilities. The assessment covers 1.5 T MRI scanners at Hospital Canselor Tuanku Muhriz (HCTM) and Hospital Pakar Kanak-Kanak UKM (HPKK), and 3 T scanners at the National Cancer Institute / Institut Kanser Negara (IKN), Pusat Pengimejan Diagnostik Nuklear (PPDN), and HCTM. Magnetic field intensities were recorded using a Magnetometer HP-01 provided by the Medical Radiation Surveillance Division (BKRP), Ministry of Health Malaysia, and visualised using MATLAB to model spatial field dispersion. Statistical tools, including Box and Whisker plots and the Shapiro-Wilk test, were employed to analyse magnetic field uniformity and containment. Specifically, 1.5 T scanners at HCTM and HPKK, and 3.0 T scanners at IKN, PPDN, and HCTM, each displayed distinct SMFs propagation profiles. These findings align with earlier studies conducted in Italy, confirming that magnetic field distributions near the magnet core can differ substantially based on scanner model and site-specific installation variables—even when B₀ remains constant. Notably, HCTM exhibited superior SMFs confinement, with lower standard deviation and a narrower distribution range, suggesting better shielding design. This enhances occupational safety in zones where radiographers frequently operate. The results reinforce the need for site-specific SMFs assessments and optimised shielding practices to maintain safe MRI environments for both staff and patients